Missed Capitellar Fracture Caused by Avoidance of Radiological Evaluation in Pregnancy - Barış Polat; Ramadan Özmanevra; Deniz Aydın; Enes Sarı; Mehmet Yalçınozan (Case Reports in Orthopedics)
In this paper, we report a pregnant woman with a missed capitellar fracture of the elbow, who was treated successfully with open reduction and internal fixation using two headless screws. A 29-year-old 6-month pregnant woman presented to the emergency department due to a history of falling on her outstretched hand. A long-arm splint was applied without radiological evaluation due to pregnancy. She came to the orthopaedics and traumatology outpatient clinic 6 weeks after trauma and her examination after splint removal revealed pain and restriction in the elbow joint movements. Radiography was taken by using a lead shield in order to protect the fetus. Radiographs showed a displaced osteochondral capitellar fracture. Using the posterolateral approach as described by Kocher, the fracture was fixed using headless canulated compression screws. The follow-up examination showed excellent functional and radiological results. Radiological evaluation should not be avoided in case of obvious fracture findings after trauma even in case of pregnancy. It is also highlighted that good results in terms of union and functional recovery can be achieved with open reduction and headless compression screw fixation followed by early rehabilitation even in delayed treatment of capitellum fractures.